Effect of remote monitoring on clinical outcomes in European heart failure patients with an implantable cardioverter-defibrillator: secondary results of the REMOTE-CIED randomized trial - Chiu, Cheyenne S. L.; Timmermans, Ivy; Versteeg, Henneke; Zitron, Edgar; Mabo, Philippe; Pedersen, Susanne S.; Meine, Mathias (Europace, 2021)
Remote patient monitoring (RPM) systems offer a promising alternative to conventional In-Clinic check-ups, hereby reducing unnecessary clinic visits. Especially with the rise of the COVID-19 pandemic, this reduction is of paramount importance. Regarding the association between RPM and clinical outcomes, findings of previous studies have been inconsistent. The aim of this study is to elucidate the effect of partly substituting In-Clinic visits by RPM on clinical outcomes in implantable cardioverter-defibrillator (ICD) patients.The study included 595 heart failure patients (LVEF ≤35%; NYHA Class II/III) implanted with an ICD compatible with the Boston Scientific LATITUDE™ system. Participants were randomized to RPM plus an annual In-Clinic visit or 3-6 months In-Clinic check-ups alone. The investigated endpoints after 2 years of follow-up included a composite of all-cause mortality and cardiac hospitalization, mortality and cardiac hospitalization as independent endpoints and ICD therapy. The incidence of mortality and hospitalization did not differ significantly as independent, nor as composite endpoint between the RPM and In-Clinic group (all Ps <0.05). The results were similar regarding ICD therapy, except for appropriate ICD therapy (odds ratio 0.50; 95% confidence interval 0.26-0.98; P = 0.04). Exploratory subgroup analyses indicated that the effect of RPM differs between patients with specific characteristics, i.e. ≥60 years and permanent atrial fibrillation (all Ps < 0.05).RPM is non-inferior to conventional In-Clinic visits regarding clinical outcomes. Routine In-Clinic follow-up may partly be substituted by RPM without jeopardizing safety and efficiency, and thus reducing unnecessary In-Clinic visits.NCT01691586.
Gesehen am 19.05.2022